Networked Learning: An Educational Paradigm for the Age of Digital Networks - Jones, Christopher (Springer, 2016)
This book posits the idea that networked learning is the one new paradigm in learning theory that has resulted from the introduction of digital and networked technologies. It sets out, in a single volume, a critical review of the main ideas and then articulates the case for adopting a networked learning perspective in a variety of educational settings. This book fills a gap in the literature on networked learning. Although there are several edited volumes in the field there is no other monograph makes the academic case and provides the academic context for networked learning. This volume accomplishes three main goals. First, it assists researchers and practitioners in acquainting themselves with the field. Second, it provides resources for reference and guidance to those not well acquainted with the field. Finally and most powerfully, it also allows for the consolidation of a field that is truly multidisciplinary in a way that maintains coherence and consistency.